Os efeitos da governança corporativa sobre a informação assimétrica - Moreiras, Luiz Maurício Franco (2010)
In December 2000, Bovespa created a list differentiating companies that voluntarily accepted corporate governance practices in addition to those required by the CVM. The purpose of the innovation was to develop the relationship between companies and their investors, reducing the asymmetry of information, giving greater certainty to investors and thereby encouraging the funds invested in capital market. This study assessed the initiative made by Bovespa, therefore was applied several statistical and econometric tests, that differentiate company as a governance policy adopted. The database has a total of 326 companies that were analyzed from 1996 to 2008. The tests indicate the existence of a clear relation between the governance and the asymmetry of information. Companies that belong to the markets with more restrictive governance policies (New Market, Level 2 and Level 1) have fewer information asymmetries. The results show the formation of a market with different characteristics to the traditional Bovespa. The companies that suffer major restrictions configure a more secure institutional environment. Therefore, the initiative of Bovespa to differentiate the market according to the degree of governance brought positive contributions to the improvement of access to information, which means a safer market for shareholders.